Back to the future: relating the development of episodic future thinking to cognitive and affective individual differences and to motivational relevance in preschoolers. Issue 3 (16th March 2021) - Opriş, Alexandra M.; Cheie, Lavinia; Visu-Petra, Laura
ABSTRACT: Episodic future thinking (EFT) represents the ability to mentally simulate scenarios that will occur in our personal future. In the current study, we used the item choice paradigm, which puts chidren in a problematic situation and requires them to envision a solution by selecting one of various items. This ability was assessed in a sample of 92 preschoolers (3–6 years old), taking into account individual differences in age, gender, cognitive (verbal abilities, EFT memory) and affective (anxiety) factors, as well as contextual factors (motivational relevance). Findings indicate developmental progress in preschoolers' foresight and in their retrospective memory for the item choice problems. The motivational valence of the EFT task played a significant role, as children performed better in the motivationally positive condition, as compared to the neutral and negative ones. However, older children had better performance than younger ones on the motivationally aversive tasks, becoming comparable to their performance in the motivationally appetitive condition. Finally, higher social anxiety was negatively related to children's EFT performance in the aversive condition, when they anticipated negative social exposure. In conclusion, EFT was explained by age-related improvements, the motivational valence of the situation and by individual differences in social anxiety, which is highly relevant for educational and therapeutic practices.